Supplementing prairie hay rations with urea and trace minerals - Smith, K.F.; Richardson, D.; Loeppke, D.W.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The trace minerals, cobalt, iodine, copper, and zinc, were added to a prairie hay-limited sorghum grain ration in an effort to improve utilization of prairie hay. Since increased quantities of urea are being successfully used in high-energy rations, its value as a protein extender in a primarily prairie hay ration was tested.
Keywords: Beef; Prairie hay; Urea; Trace minerals